Mentally tough behaviour in extreme environments: perceptions of elite high-altitude mountaineers. Issue 3 (27th May 2019) - Crust, Lee; Swann, Christian; Allen-Collinson, Jacquelyn
ABSTRACT: Although numerous studies have examined the importance of mental toughness (MT) in sport, relatively few studies have examined mentally tough behaviours . We therefore sought to identify the indicative behaviours of elite, mentally tough mountaineers, an under-researched group, by examining participants' experiences and perceptions. Phenomenological interviews were conducted with 17 experienced high-altitude mountaineers ( M age  = 45 years). Results were organised into three general dimensions, which concerned: (i) preparatory behaviours, (ii) social/interpersonal behaviours and (iii) intrapersonal behaviours. Behaviours such as meticulous preparation, consistently high work rates, quick recovery following setbacks, and thriving in challenging situations were found to be broadly consistent with previous research. Nevertheless, novel and nuanced themes, such as pragmatic perseverance, selflessness and tolerance emerged as salient new findings. Results are discussed in the context of existing models of MT and in relation to the challenges of measuring mentally tough behaviour.